Pengaruh Promosi Berbasis Wisata Edukasi dan Inovasi Produk Batik Pecel Terhadap Volume Penjualan - Dika Nur Idayati; Raya Sulistyowati (Universitas Negeri Padang, 2022)
MSMEs are global organizations that carry out various important functions in economic development, including Indonesia which is one of the developing countries in the world. MSMEs in Indonesia over time continue to increase. However, during the pandemic there has been a very drastic decline. One of them is at the Pure Batik Gallery. The company's efforts to deal with this phenomenon are by carrying out new promotions and innovations such as conducting promotions based on educational tours and new innovations for batik pecel. With these problems, researchers have a goal in conducting research to better understand the impact of tourism-based promotion, education, and batik production innovation on sales volume simultaneously and sequentially. The method used to determine the relationship between variables and independent variables in an experiment using quantitative methods. The sample size for this research was generated using the basic random sampling technique with a sample size of about 100 people. Multiple linear regression analysis, t test, and F test were used for data analysis. The results of this study indicate that partially and simultaneously the promotional variables based on educational tourism, and the innovation variables in the production of batik pecel have a significant effect on sales volume.